Vocal fold lesions in the pediatric age group: our experiences at a tertiary care teaching hospital of India - Swain, Santosh K.; Dubey, Debasmita (International Journal of Contemporary Pediatrics, 2022)
Background: Vocal fold lesions are commonly found in the pediatric age group. The lesions of the vocal fold among children are variable. The laryngoscopic examination is needed for the identification of the vocal fold lesions. The objective of this study is to find out the different vocal fold lesions, clinical presentations, and diagnoses of the vocal fold lesions. Methods: The children aged from 5 to 18 years diagnosed with vocal fold lesions were included in this study. The study was conducted between June 2017 to July 2022. All the children with vocal fold lesions were subjected to video laryngoscopy for assessment of the larynx. Results: There were 156 children diagnosed with vocal fold lesions. The majority of this study’s participants were male children (52.56%). The most common symptom was hoarseness. Most common vocal fold lesion was vocal fold nodule (43.58%). Voice abuse was the most common etiological factor behind the vocal fold lesions. Out of 156 children with vocal fold lesions, 72 children (46.15%) underwent microlaryngeal surgery under anesthesia. Voice therapy was given to all the children along with vocal hygiene care. Conclusions: Vocal fold lesions are often found among children. Dysphonia is the commonest clinical presentation of children with vocal fold lesions. Microlaryngeal surgery and voice therapy are two important options for the treatment of vocal fold lesions in pediatric patients.